Substance misuse and violent crime: Swedish population study - Grann, M; Fazel, S (BMJ Publishing Group, 2004)
Many studies have reported strong associations between substance misuse and violent crime. But the population impact of people diagnosed with substance use disorders on such crime is not known. Calculating the population impact and the relative importance of different classes of drugs is necessary to estimate the likely public health effect of any developments in services and treatment interventions in preventing violent crime. To investigate the overall impact of substance misuse on violent crime, we estimated the population attributable risk using data from high quality national psychiatric and crime registers in Sweden from 1988 to 2000.